Non-invasive body condition monitoring and relationships between thermal responses and behaviour in captive and wild Nile crocodiles (Crocodylus niloticus) - Webb, E.C. (Edward Cottington) (University of Pretoria, 2025)
Thesis (PhD (Animal Science))--University of Pretoria, 2024.